South Asia Economic Focus, Spring 2020 : The Cursed Blessing of Public Banks - World Bank (Washington, DC: World Bank, 2020)
The unprecedented COVID-19 crisis comes with a dire economic outlook. South Asia might well experience its worst economic performance in 40 years. The harsh reality of inequality in South Asia is that poor people are more likely to become infected with the coronavirus, as social distancing is difficult to implement for them. They also have less access to health care or even soap, are more likely to have lost their job, and are more vulnerable to spikes in food prices. The unfolding economic crisis is unique in several ways. This report estimates that regional growth will fall to a range between 1.8 and 2.8 percent in 2020, down from 6.3 percent projected six months ago. The dire forecast is based on the analysis of several adverse impacts. South Asia finds itself in a perfect storm. Tourism has dried up, supply chains have been disrupted, demand for garments has collapsed, consumer and investor sentiments have deteriorated, international capital is being withdrawn and inflows of remittances are being disrupted. On top of the deterioration of the international environment, the lockdown in most countries has frozen large parts of the domestic economy. Public banks, discussed in the focus chapter of this edition, were at the center of weaknesses in financial sectors that accumulated during recent years. However, during this crisis, they might be part of the solution by providing countercyclical lending to the most vulnerable parts of the economy.